Closing the Nutrition Impact Gap Using Program Impact Pathway Analyses to Inform the Need for Program Modifications in Mexico's Conditional Cash Transfer Program. (3rd December 2019) - García-Guerra, Armando; Neufeld, Lynnette M; Bonvecchio Arenas, Anabelle; Fernández-Gaxiola, Ana C; Mejía-Rodríguez, Fabiola; García-Feregrino, Raquel; Rivera-Dommarco, Juan A
ABSTRACT: Background: Mexico's Prospera-Oportunidades-Progresa Conditional Cash Transfer Program (CCT-POP) included the distribution of fortified food supplements (FFS) for pregnant and lactating women and young children. Rigorous evaluations showed significant impacts on nutrition outcomes but also substantial gaps in addressing nutrition problems. Objectives: To highlight the program design-related and implementation-related gaps and challenges that motivated further research and the eventual design and roll-out of a modified nutrition component for CCT-POP. Methods: We used a program impact pathway approach to highlight the extent and quality of implementation of CCT-POP, and its impact on nutrition outcomes. We drew on previously published and new primary data, organized into 3 sources: impact evaluations, studies to inform reformulation of the FFS, and a longitudinal follow-up study using qualitative and quantitative methods to document FFS use and the dietary intake of women and children. Results: Despite positive impacts, a high prevalence of malnutrition persisted in the population. Coverage and use of health services improved, but quality of care was lacking. Consumption of FFS among lactating women was irregular. Micronutrient intake improved among children who consumed FFS, but the pattern of use limited frequency and quantity consumed. Substantial diversity in the prevalence of undernutrition was documented, as was an increased risk of overweight and obesity among women. Conclusions: Three key design and implementation challenges were identified. FFS, although well accepted for children, had limited potential to substantially modify the quality of children's diets because of the pattern of use in the home. The communications strategy was ineffective and ill-suited to its objective of motivating FFS use. Finally, the program with its common design across all regions of Mexico was not well adapted to the special needs of some subgroups, particularly indigenous populations. The studies reviewed in this paper motivated additional research and the eventual redesign of the nutrition component.